Toxic Effects of Bisphenol A on Fat Deposition, Weight Gain, in Rats - Abdulhasan, Zaid Abdulhamza; Hussein, Haider Mashkoor (American Journal of Biology and Natural Sciences, 2026)
It has been shown that bisphenol A (BPA) is associated with major alterations in lipid metabolism and the buildup of fat. There is a significant dose-response connection between exposure to BPA and a rise in body weight, notably in animal models. This association in particular has been shown in animal models. The substance acts as a substitute for estrogen, which causes disruptions in endocrine functioning and encourages adipogenesis. Adipogenesis is the process by which preadipocytes transform into mature fat cells, which ultimately results in increased fat accumulation. BPA exposure during critical developmental periods, such as prenatal and postnatal, has been shown to result in an increase in adipose tissue mass, triglyceride levels, and cholesterol levels, as well as a decrease in high-density lipoprotein (HDL) levels, which is indicative of a metabolic disturbance. These findings were derived from studies conducted on rats. The results of this study provide credence to the concept that bisphenol A (BPA) functions as an obesogenic, giving rise to the possibility that it may contribute to metabolic illnesses such as insulin resistance and type 2 diabetes. It was noted that the modifications in lipid metabolism and the promotion of fat storage were present throughout a range of doses of BPA, with the effects being more significant at higher doses. Because of the effects that exposure to BPA has on body weight and fat deposition, it seems that even low-level exposure to BPA may contribute to the development of metabolic health problems over the long run.